A New Technique of Oophoropexy: Folding and Fixating of Utero-Ovarian Ligament to Round Ligament in a Patient with Reccurrent Ovarian Torsion - Mehmet Obut; Uğur Değer (Hindawi Limited, 2019)
Introduction. Most cases of ovarian torsion occur in the reproductive age and many are related to ovarian and paraovarian masses. If it occurs without any subtle anatomic etiology or ovarian and paraovarian masses, recurrence of ovarian torsion is more likely. Recurrent left ovarian torsion is much less common than recurrent right ovarian torsion. The authors describe a rare case with their new ovarian fixation technique. Case and Method. A 21-year-old female patient with polycystic ovarian syndrome had a 7th recurrence of left ovarian torsion. Although ovarian fixation was performed in addition to detorsion at the 5th and the 6th laparoscopic surgeries, it had failed. Due to recurrence ovarian torsion after ovarian fixation, the authors performed a different technique:folding the utero-ovarian ligament which folded on itself. The distal part of the utero-ovarian ligament with the ovary was both fixed to the proximal part of the round ligament which was adjacent to the uterus. Conclusion. Although a wide range of oophoropexy methods have been described in the literature, the best method remains a matter for debate. This technique can be performed even when the ovarian tissue is necrotic. Because of this, we think that this technique is useful and effective technique.